Regulation of surface expression of the granulocyte/macrophage colony-stimulating factor receptor in normal human myeloid cells. - Cannistra, S A (1990)
Recombinant human granulocyte/macrophage colony-stimulating factor (GM-CSF) exerts stimulatory effects on hematopoietic cells through binding to specific, high-affinity receptors (Kd = 30-100 pM). By using radiolabeled GM-CSF with high specific activity, we have investigated the factors and mechanisms that regulate GM-CSF receptor expression in normal human neutrophils, monocytes, and partially purified bone marrow myeloid progenitor cells. The neutrophil GM-CSF receptor was found to rapidly internalize in the presence of ligand through a mechanism that required endocytosis. Out of a large panel of naturally occurring humoral factors tested, only GM-CSF itself, tumor necrosis factor, and formyl-Met-Leu-Phe were found to down-regulate neutrophil GM-CSF receptor expression after a 2-hr exposure at biologically active concentrations (95% +/- 1%, 34% +/- 5%, 48% +/- 8% receptor down-regulation, respectively). GM-CSF also down-regulated its own receptor on monocytes and myeloid progenitor cells. Since formyl-Met-Leu-Phe is known to stimulate neutrophil protein kinase C activity, we also tested the ability of protein kinase C agonists to modulate GM-CSF receptor expression. Phorbol 12-myristate 13-acetate, bryostatin-1, and 1,2-dioctanoylglycerol were found to induce rapid down-regulation of the GM-CSF receptor in neutrophils, monocytes, and partially purified myeloid progenitor cells, suggesting that this effect may be at least partially mediated by protein kinase C. These data suggest that certain activators of neutrophil function may negatively regulate their biological effects by inducing down-regulation of the GM-CSF receptor.